2021
DOI: 10.1021/acs.accounts.1c00397
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Transmembrane Ion Channels Formed by Multiblock Amphiphiles

Abstract: Conspectus Transmembrane proteins located within biological membranes play a crucial role in a variety of important cellular processes, such as energy conversion and signal transduction. Among them, ion channel proteins that can transport specific ions across the biological membranes are particularly important for achieving precise control over those processes. Strikingly, approximately 20% of currently approved drugs are targeted to ion channel proteins within membranes. Thus, synthetic molecules that can mim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…Over the last decade, our research group has developed a series of linear-shaped multiblock amphiphiles that can self-assemble within the lipid bilayer membranes to form supramolecular ion channels. 46 We also demonstrated that appropriate chemical modifications enabled these ion channels to be responsive to ligand molecules, 32,33,47 membrane potential, 33 and mechanical forces applied to the membranes. 44 The multiblock structures are particularly attractive for their combination of rigid aromatic units and flexible oligo(ethylene glycol) chains reminiscent of the structure of natural multipass transmembrane proteins, contributing to their stimuli-responsive ion transport properties.…”
Section: ■ Introductionmentioning
confidence: 83%
“…Over the last decade, our research group has developed a series of linear-shaped multiblock amphiphiles that can self-assemble within the lipid bilayer membranes to form supramolecular ion channels. 46 We also demonstrated that appropriate chemical modifications enabled these ion channels to be responsive to ligand molecules, 32,33,47 membrane potential, 33 and mechanical forces applied to the membranes. 44 The multiblock structures are particularly attractive for their combination of rigid aromatic units and flexible oligo(ethylene glycol) chains reminiscent of the structure of natural multipass transmembrane proteins, contributing to their stimuli-responsive ion transport properties.…”
Section: ■ Introductionmentioning
confidence: 83%
“…Inspired by this structural feature, researchers have used a variety of multiblock amphiphiles to construct folded scaffolds that imitate the conformation and function of supramolecular transmembrane channels. [ 192–194 ] Muraoka et al. reported the construction of a three‐transmembrane ion channel through the folding of multiblock amphiphiles.…”
Section: Nps As Mimics Of Protein Scaffoldsmentioning
confidence: 99%
“…Inspired by this structural feature, researchers have used a variety of multiblock amphiphiles to construct folded scaffolds that imitate the conformation and function of supramolecular transmembrane channels. [192][193][194] Muraoka et al reported the construction of a three-transmembrane ion channel through the folding of multiblock amphiphiles. The multiblock amphiphiles were composed of alternatively connected oligoethylene glycol (oligoEG) chains and rigid 3,3′-dimethyl-5,5′-dis(phenylethynyl)-2,2′-bipyridine (BPBP) units as the hydrophilic and hydrophobic moieties, respectively.…”
Section: Polymer-based Scaffoldsmentioning
confidence: 99%
“…We previously reported multiblock amphiphilic compounds consisting of aromatic hydrophobic units and hydrophilic oligo(ethylene glycol) chains that have high affinity to lipid bilayer membranes. 44 Some of these molecules also work as trans-membrane transporters. 45 Since oligo(ethylene glycol) units are biocompatible, 46 we designed the multiblock molecule AnP2-OEG by combining a diaminoanthracene unit with octa(ethylene glycol) (OEG) chains to allow high membrane permeability while maintaining low cytotoxicity (Figure 1).…”
Section: Introductionmentioning
confidence: 99%